MENYOAL IZIN POLIGAMI BAGI PNS - Khoirin, Nur (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
polygamy is restricted opportunities (especially for civil servants) are used based on the number of cases of irregularities and imbalances polygamous family. As polygamy was illegal, the outbreak of the household, the absence of economic security and justice, oppression of women, and displaced children. However, the regulations concerning polygamy (UUP-1/1974, PP-9/1975, and PP-10/1983) are relatively obsoloete. Therefore, it is questionable again, if the rules are restrictive and prohibit polygamy still relevant and should continue to be enforced? Is not it considered contrary to human rights because the government is too far away to intervene in the private sphere? Is polygamy still considered socially deviant acts, or exactly the opposite of polygamy is a laudable behavior to avoid deviant behavior? Polygamy is the unalienable right of every person who should be protected and fairly distributed. Laws that conflict with basic human instinct would not be effective running, and if enforced would cause bad effects and aberrations